RANCANG BANGUN SISTEM LOKER OTOMATIS MENGGUNAKAN QRCODE DAN LAMPU UV DISINFEKTAN - Estrada, Novesel; Rafli Pratama, Muhammad; Ariyadi, Tamsir (LPPM Universitas Putera Batam, 2025)
As technology advances, the level of intelligence in humans increases, so humans always want to create progressive innovations, but besides that, it can also give rise to crime in society. Therefore, security aspects are very much needed in various sectors of life today. One of them is the locker security system which can influence criminal acts. A locker is a place for storage that usually has a lock, which is used to store or place valuable items. One of the facts is that there is often theft and loss of items at places where lockers are rented or borrowed. Thieves can easily open the locker lock using a piece of wire or other artificial keys. This research designs and builds a locker door security system consisting of QRcode sensors, solenoid locks, UV lights, Arduino and other sensor devices. The result of this research is an implementation of a locker security system that can open and close locker locks automatically using Arduino Uno which can provide automatic lock security with a better level of security such as the use of an automatic lock that uses a QRcode scan sensor which only the owner can open by pasting the QRcode code, and additional automatic locks such as a password keypad to open the locker.